Self-diagnostic of the competence of scientific-pedagogical worker: aspect of educational work - KomyshanА.; ZhukovaО.; Panfilov, Y.; Riadnova, A. (Scientific notes of the pedagogical department, 2021)
The article deals with the problem of self-diagnostic of the competence of a scientific-pedagogical worker: aspect of educational work. Based on the analysis of approaches to monitoring in education and diagnostic in education, it was found that the interest in the issues of quality of higher education, objective assessment of the activities of subjects and structural units of higher education, as well as innovative approaches to the management of quality of education, in particular, through the management of quality of activities of scientific and teaching staff is growing. On the basis of scientific generalizations and the results of empirical studies, significant signs of monitoring and diagnostics in higher education system are highlighted and it is determined that educational monitoring and diagnostic in higher education should be considered as a kind of regular observation process using certain signs, indicators, criteria, factors and scales. On view of the analysis of information sources, it was found that pedagogical diagnostic is used in such objects of educational environment as: training sessions; individual work of students; teaching methods; curricula and programs; forms of education; technology of organization of the educational process; schedule of classes; qualimetry of teachers; study of advanced teaching experience; methodical work; practical training, etc. Namely here it gives a tangible increase in efficiency. The essence of the concept of “self-diagnostic of educational work of a scientific-pedagogical worker” is formulated. Taking into account the worked out sources of information and own pedagogical experience, as well as interviews with students, the key directions of self-diagnostic of the educational work of a scientific and pedagogical worker are determined. Four key organizational and pedagogical conditions for self-diagnostic of a scientific-pedagogical worker in educational work are stated. The methodology of self-diagnostic of a scientific-pedagogical worker for educational work is substantiated. A questionary of an anonymous survey of students on self-diagnostic of the state of educational work by a scientific-pedagogical worker is presented. The main ways of improving the skill of a scientific-pedagogical worker in educational work are determined on the basis of the results of anonymous questioning of students.